Floating ZnO QDs-Modified TiO2/LLDPE Hybrid Polymer Film for the Effective Photodegradation of Tetracycline under Fluorescent Light Irradiation: Synthesis and Characterisation - Anwar Iqbal; Usman Saidu; Farook Adam; Srimala Sreekantan; Noorfatimah Yahaya; Mohammad Norazmi Ahmad; Rajabathar Jothi Ramalingam; Lee D. Wilson (Molecules)
In this work, mesoporous TiO2-modified ZnO quantum dots (QDs) were immobilised on a linear low-density polyethylene (LLDPE) polymer using a solution casting method for the photodegradation of tetracycline (TC) antibiotics under fluorescent light irradiation. Various spectroscopic and microscopic techniques were used to investigate the physicochemical properties of the floating hybrid polymer film catalyst (8%-ZT@LLDPE). The highest removal (89.5%) of TC (40 mg/L) was achieved within 90 min at pH 9 due to enhanced water uptake by the LDDPE film and the surface roughness of the hybrid film. The formation of heterojunctions increased the separation of photogenerated electron-hole pairs. The QDs size-dependent quantum confinement effect leads to the displacement of the conduction band potential of ZnO QDs to more negative energy values than TiO2. The displacement generates more reactive species with higher oxidation ability. The highly stable film photocatalyst can be separated easily and can be repeatedly used up to 8 cycles without significant loss in the photocatalytic ability. The scavenging test indicates that the main species responsible for the photodegradation was O2●−. The proposed photodegradation mechanism of TC was demonstrated in further detail based on the intermediates detected by LC-time-of-flight/mass spectrometry (LC/TOF-MS).